Elemen pedagogi dan teknologi dalam reka bentuk MOOC - Noor Toheerah, Binti Abu Sammah (Universiti Malaysia Sarawak (UNIMAS), 2017)
The purpose of this study is to examine the elements of pedagogical and technological in the design of the MOOC. In this study a total of 100 respondents consists ofstudents and lecturers at University Malaysia Sarawak. This study was conducted using a quantitative methods. The results obtained through this study, shows the most important element in the design MOOC is a Instructional Design Category in pedagogical elements, while for the technology elements also found that video content category has a major role in the involvement of students and lecturers in the MOOC. As a conclusion, both of these elements are important in the online learning because the level of agreement among students and lecturers is a main factor in the successful for designing MOOC.